Equine Blood Microbiome in a Cohort of Clinically Healthy Trail Riding Horses - Noel Simms; Joseph J. Bertone; Tonatiuh Melgarejo; Caitlin O'Shea; Annika Linde (Journal of Veterinary Internal Medicine)
ABSTRACT Background Emerging research suggests the presence of a blood microbiome in clinically healthy individuals. Characterizing bacterial composition and abundance in blood from a group of healthy horses is of clinical interest. Hypothesis/Objectives Horses in a closed herd environment will have blood microbiomes with similarities among individuals. Animals Twenty trail‐riding horses of different breeds and ages living in relative isolation on a dry lot pasture in Colorado at 7680 ft elevation. Methods Cross‐sectional study. Blood was collected from the jugular vein into serum, blood collection, and EDTA tubes. Samples were submitted to external laboratories for microbiome analysis and routine blood tests (CBC, serum biochemistry). Results Venous blood is not sterile in healthy horses. A total of 293 bacterial genera were identified in these samples, whereas most horses had 55 to 70 genera. The most dominant taxa were Gardnerella, Sporomusaceae, Kapabacteriales, Beijerinckiaceae, and Phascolarctobacterium. Principal coordinate analysis, investigating microbial structure diversity, identified large variability with no obvious clustering, indicating dissimilarity among bacterial populations in different horses. All blood samples contained genera with pathogenic potential for horses, such as Bacteroides spp., Clostridium spp., Peptostreptococcus spp., Streptococcus spp., and Staphylococcus spp. Conclusions and Clinical Importance Clinically healthy horses had a diverse blood microbiome. Despite the relative isolation of the horses, their blood microbiota varied markedly among individuals. Investigating the bacteria in clinically healthy horse blood provides new insight into possible microbiome shifts that may result in clinical disease.